DAMPAK MEDIA SOSIAL TERHADAP PRESTASI BELAJAR PESERTA DIDIK - Anik Suryaningsih (PENDIDIKAN SAINS DAN TEKNOLOGI, 2020)
Social media not for learning purposes. Social media is very influential for students to support learning achievement. Learning achievement is a result of learning achieved after participating in the process of learning activities. Learning achievements can also be shown in the form of numbers or values, to obtain the achievement of learning achievement requires a maximum effort. Moreover, in teaching and learning activities a process of organizing, organizing the environment around students is needed so that it can foster and encourage students to do the learning process. The role of parents and teachers in schools is expected to help students in limiting themselves in social media. The purpose of the author to write this is to determine the effect of: (1) learning achievement; (2) Social Media; (3) effect negative and positive; (4) the role of teachers in schools on the impact of the use of social media.